Martingale Approach for Markov Processes in Random Environment and Branching Markov Chains (Resenhas do Instituto de Matemática e Estatística da Universidade de São Paulo, 2014)
In this paper we study random walks with branching (BRW), and two examples of countable Markov chains in random environment which are a one dimensional random walk and a random string.